Enhancing coping skills of dormers through cognitive behavior therapy - Marcelino, Arlaine Joy D.; Vinluan, Lorelei R.; Gomez, Marie Grace A.; Guevarra, Shirley V. (Quezon City College of Education, University of the Philippines Diliman, 2015)
In the Residence Halls are anxious ambivalent dormers who often feel reluctant about becoming close to others and are overwhelmed by negative thoughts and feelings during a stressful event. These dormers have difficulty coping with their problems as supported by their Coping Strategies Inventory scores. They avoid or withdraw from their problems. To enhance their coping skills, eight anxious ambivalent dormers, 2 females and 6 males, with ages 18-19 years old served as the participants of the case study. It was anchored on the theory of Meichenbaum known as the Stress Inoculation Training (SIT). It is a three-stage model that includes conceptual phase, skills acquisition phase and the application phase. After the 12 group counseling sessions, data gathered were analyzed using the mixed -method. Wilcoxon Signed- Rank Test was used to check if there is a significant difference in the pre and post-test scores of the dormers after the intervention. Thematic analysis was also used to identify the patterns/ categories in the responses of the participants. CBT was found effective in enhancing the coping skills of the dormers. At the end of the session, dormers were more engaged rather than passive in handling their problems.
Thesis
Includes bibliographical references (113-115 leaves).
Keywords: Cognitive therapy; Behavior therapy for teenagers -- Philippines -- Manila Metropolitan Area; Behavior therapy -- In-adolescence.; Dormitory life -- Philippines -- Manila Metropolitan Area